The impact of digital development on human well being and vice versa - Eleni Laitsou; Apostolos Xenakis (International Telecommunications Society (ITS), 2023)
This study examines the relationship between human well-being and digital development, focusing on the case study of EU-27 countries during the period from 2018 to 2021. The investigation utilizes two key indicators: the Digital Economy and Society Index (DESI), which assesses the digital performance of Europe, and the Human Development Index (HDI), a United Nations metric for measuring citizen well-being. The primary objective of this study is to determine the relationship between a country's DESI and HDI values and to explore the possible categorization of countries based on these indicators over the study period. Additionally, the impact of the Covid-19 pandemic on these indicators is examined. According to the findings a better understanding of the dynamic interplay between digital development and human well-being is achieved, offering valuable insights for policymakers and researchers.
Keywords: 330; Digital Economy and Society Index (DESI); Human Development Index (HDI); European countries; Covid-19 pandemic; regression analysis